Isolation, characterization and differentiation of cells expressing pluripotent/multipotent markers from adult human ovaries - Stimpfel, Martin; Skutella, Thomas; Cvjeticanin, Branko; Meznaric, Marija; Dovc, Peter; Novakovic, Srdjan; Cerkovnik, Petra; Vrtacnik-Bokal, Eda; Virant-Klun, Irma (Cell & tissue research, 2013)
Pluripotent stem cells are still generally accepted not to exist in adult human ovaries, although increasing studies confirm the presence of pluripotent/multipotent stem cells in adult mammalian ovaries, including those of humans. The aim of this study is to isolate, characterize and differentiate in vitro stem cells that originate from the adult human ovarian cortex and that express markers of pluripotency/multipotency. After enzymatic degradation of small ovarian cortex biopsies retrieved from 18 women, ovarian cell cultures were successfully established from 17 and the formation of cell colonies was observed. The presence of cells/colonies expressing some markers of pluripotency (alkaline phosphatase, surface antigen SSEA-4, OCT4, SOX-2, NANOG, LIN28, STELLA), germinal lineage (DDX4/VASA) and multipotency (M-CAM/CD146, Thy-1/CD90, STRO-1) was confirmed by various methods. Stem cells from the cultures, including small round SSEA-4-positive cells with diameters of up to 4 μm, showed a relatively high degree of plasticity. We were able to differentiate them in vitro into various types of somatic cells of all three germ layers. However, these cells did not form teratoma when injected into immunodeficient mice. Our results thus show that ovarian tissue is a potential source of stem cells with a pluripotent/multipotent character for safe application in regenerative medicine.